2019
DOI: 10.24953/turkjped.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cardiomyopathy-tachycardiomyopathy in children

Abstract: Tachycardia-induced cardiomyopathy (tachycardiomyopathy) is defined by the presence of a sustained tachycardia that results in left ventricular systolic dysfunction. Restoration of cardiac function is dependent on the control of tachyarrhythmias. We report a series including ten children with tachycardia-induced cardiomyopathy with different etiologies. The medical records of patients with tachycardiomyopathy who were managed in a Pediatric Cardiology Clinic between the years of 2014-2017 were reviewed retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…It has also been shown that many children with tachyarrythmia tend to have antecedent history of infection and nonspecific symptoms such as dyspnea, palpitation, and cough which mimic diagnosis of myocarditis and DCM. 18 The improvement in cardiac function over time with normalization in heart rate is diagnostic of tachycardiomyopathy. The median time recovery of cardiac function in tachycardia induced cardiomyopathy is <2 months 19 Children with SVT in our series had features of myocardial dysfunction in the form of cardiomegaly, shock, reduced EF, and raised CK-MB.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that many children with tachyarrythmia tend to have antecedent history of infection and nonspecific symptoms such as dyspnea, palpitation, and cough which mimic diagnosis of myocarditis and DCM. 18 The improvement in cardiac function over time with normalization in heart rate is diagnostic of tachycardiomyopathy. The median time recovery of cardiac function in tachycardia induced cardiomyopathy is <2 months 19 Children with SVT in our series had features of myocardial dysfunction in the form of cardiomegaly, shock, reduced EF, and raised CK-MB.…”
Section: Discussionmentioning
confidence: 99%
“…Once HR is normalized (for example, medical treatment, electrical cardioversion and radiofrequency ablation), the clinical and functional recovery of the heart is rapid and does not usually extend beyond 6 months. 1 , 18 , 40 However, the possibility of recurrence 1 , 2 , 66 exists (unusual in children 42 ) possibly linked to the persistence of interstitial fibrosis regardless of LVEF improvement. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“… 6 , 35 , 38 Once control of tachyarrhythmia is effective, the greatest improvement in LVEF is found during the first month, whilst its complete recuperation can extend to the second or third month (in general, not more than 6 months). 1 , 18 , 41 It has also been observed that patients who present a more significant improvement are those with a worse pre-treatment LVEF 42 whilst, in children, TCMP typically makes a complete recovery with appropriate treatment. 1 , 43 …”
Section: Reviewmentioning
confidence: 99%
“…Management of TIC is directed towards the control of the arrhythmia either by rate control or return to sinus rhythm which can be achieved through cardioversion, antiarrhythmic drugs, and/or catheter ablation. 9 Heart failure management can be also required in selected cases of incessant arrhythmias which are generally related to the longer duration of the tachycardia. In patients with TIC, ECMO can be used during the initial management of critically ill patients presenting in cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%